The Development of Augmented Reality Card Game The Ramayana Literature on Thai Subject for Prathomsuksa 6 Students School in Chanthaburi Primary Educational Service Area 1 - Katchinda, Yingyos; Srifa, Paitoon (Journal of Inclusive and Innovative Education, 2021)
The objective of this research is to 1. Develop augmented reality card games Ramayana Literature, Thai subject for PrathomSuksa VI students. 2. Study the learning achievement. 3. Study the students’ satisfaction. 4. Study the effectiveness index. The samples group of the research derived from specific selection were 26 Prathomsuksa 6 Students at Watkaowongkod School Chanthaburi Primary Educational Service Area 1. The research findings revealed that: 1.The Augmented Reality Card game had quality at very good level and the efficiency at 81.92/84.61 2.The student’s pretest and posttest scores after using the Augmented Reality Card game are different significant at .01 level. 3. The students’ satisfaction was at the highest level, 4. The affectiveness index at 0.70.